(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This paper presents a model for the use of unmanned aerial vehicles in the medical support of military formations at the tactical level. The medical support system of the Armed Forces of the Republic of Bulgaria is described and a model for the use of drones by the medical posts of military formations in combat operations is presented, emphasizing the use in the field of medical intelligence, deployed elements and minimum technical requirements for unmanned aerial vehicles to ensure the implementation of medical support tasks.